Where Do Plastic Surgery Leaders Come From? A Cross-sectional Analysis of Research Productivity - Megan M. Rodriguez, BS; Kylie R. Swiekatowski, BA; Robert C. Tung, MD; Matthew R. Greives, MD, MS; David W. Mathes, MD; Phuong D. Nguyen, MD, FACS, FAAP (Plastic and Reconstructive Surgery, Global Open)
Background:. It is increasingly apparent that plastic surgery residency applications with lengthy research publications are the new standard in applicant competitiveness. This study aims to evaluate the research history of plastic surgery program faculty leadership to understand the trends and evolution of research expectations. Methods:. The curriculum vitaes of faculty involved in residency admissions among all US Accreditation Council for Graduate Medical Education-accredited integrated and independent plastic surgery programs were reviewed. Doximity, program websites, and Scopus were used to gather information. H-index and publication count at the time of medical school and residency graduations were collected. Student t test and Pearson product-moment correlation were used for analysis. Results:. Of the 236 plastic surgeons considered, faculty averaged one publication by medical school graduation, two by general surgery residency graduation, and six by plastic surgery residency graduation. Integrated residents held more publications after medical school (1.67 versus 0.56; P = 0.09) and plastic surgery residency (8.48 versus 4.89; P = 0.01) compared with independent residents. Later plastic surgery residency graduation year correlated with more publications (P < 0.001). Chairs had higher h-indices compared with program directors and associate positions (chair: 23.7, program director: 14.7, associate: 12.2; P < 0.001). Conclusions:. The majority of faculty leaders’ research was published after residency. The emerging trend of increased research volume among plastic surgeons-in-training may be a consequence of competitive research requirements to matriculate into residency. Longer-term career follow-up of newer graduates will need to be assessed to determine whether this predicts future postgraduate productivity or if it is just the price of admission to train as a plastic surgeon.